Talent management practices and turnover intention: The role of perceived distributive justice and perceived organizational support - Supi; Noermijati; Dodi Wirawan Irawanto; Astrid Puspaningrum (Cogent Business & Management, 2023)
This study aims to analyze the effect of talent management practices on turnover intention either directly or through perceived distributive justice and perceived organizational support as mediation. The research was conducted using a quantitative approach with total sample of 397 Directorate General of Taxes employees. Analysis of research data using SMART-PLS with the result that there is an influence of talent management practices on turnover intention through perceived distributive justice and perceived organizational support. Talent management practices have been shown to increase perceived distributive justice and perceived organizational support. Turnover intention decreases because of perceived distributive justice and perceived organizational support by employees. The results of this study make a theoretical contribution to support social exchange theory, equity theory, and organizational support theory as well as make a practical contribution to HR managers of public organizations. The novelty of this research is in the form of a comprehensive model with perceived distributive justice and perceived organizational support as mediating the influence of talent management practices on turnover intention in public organizations. The results of this study answer the scarcity of studies on public organizations in Asia. The results of this study also add to the repertoire of empirical research which can be used as a reference in drawing generalizations or conclusions regarding the influence of talent management practices on turnover intention.
Keywords: 650; perceived distributive justice; perceived organizational support; talent management practices; turnover intention